The Impact of Positive and Negative Income Changes on the Height and Weight of Young Children - Buser, Thomas (Published by Oxford University Press on behalf of the World Bank, 2019)
We estimate the impact of changes in unearned income on the height and weight of young children in a developing country. As a source of income variation we use a change in the eligibility criteria for receipt of an unconditional cash transfer in Ecuador. Two years after families lost the transfer, which they had received for seven years, their young children weigh less and are shorter and more likely to be stunted than young children in families that kept the cash transfer. We find no statistically significant effect on young children's height and weight two years after gaining the cash transfer. Information on household expenditures suggests that a reduction of food expenditures by households that lost the transfer is the main mechanism behind this finding.